GAMBARAN C-REACTIVE PROTEIN (CRP) PADA LANSIA DENGAN KADAR ASAM URAT TINGGI DI SEKELADI HILIR KECAMATAN TANAH PUTIH KABUPATEN ROKAN HILIR - Eli Yusrita (Akademi Kesehatan John Paul II Pekanbaru, 2021)
Elderly defined as someone who has reached the age of 60 years or older who will experience anatomical, physiological and biochemical changes in the body, causing various health problems, one of them is uric acid which if excess, causes monosodium urate crytals in the joint space, causing severe joint paint and joint swelling (particularly in the big toe, middle foot,ankle and knee) thus causing inflamation. CRP is one of alpha globulin that rises in the blood serum after an inflammatory pocess occurs. The aims of this study to determine the description CRP in elderly with high uric acid levels. This research is a cross sectional study and sampling by purposive sampling with 22 respondents. The results of CRP in elderly patient with gout there were 16 respondents (72,7%) positive CRP and 6 respondents (27,3%) negative. Thus, it can be concluded that CRP is found in elderly people with gout as a marker of the inflammatory process.